Unfinished sympathies: Influence of individual temporal orientation on music preferences. (September 2019) - Nowack, Kati
Temporal aspects have been studied extensively within the context of music perception but insufficiently within the context of music preference. In this online questionnaire study, I investigated the impact of chronotype (morningness, eveningness) and time perspective (present, future) on music preferences. Participants ( n = 258) completed the Short Test of Music Preferences for 26 music genres, the Zimbardo Time Perspective Inventory and the Munich Chronotype Questionnaire. Principal component analysis replicated a six-component structure of music preference. Whilst preference scores were highest for intense music for all participants, I found significant effects of chronotype and time perspective on music preferences. In particular, present-oriented evening types and future-oriented morning types differed in their preferences for various music genres. Consistent with a matching hypothesis, present-oriented evening types (fast life histories) showed greater preferences for contemporary (i.e., high rhythmic complexity), sophisticated (i.e., high complexity) and electronic music (i.e., fast tempo) compared to future-oriented morning types (slow life histories; greater difficulties with temporal irregularities). Consistent with a self-regulation hypothesis, present-oriented evening types showed greater preferences than future-oriented morning types for campestral music (i.e., slow tempo and low complexity).